2018
DOI: 10.1038/s41598-018-29308-7
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids inhibit cell proliferation and induce apoptosis and autophagy through downregulation of PI3Kγ mediated PI3K/AKT/mTOR/p70S6K/ULK signaling pathway in human breast cancer cells

Abstract: Anticancer activities of flavonoids derived from Tephroseris kirilowii (Turcz.) Holub. were evaluated in human cancer cells. We isolated and identified, for the first time, eight flavonoids from T. kirilowii and found that three of them (IH: isorhamnetin, GN: genkwanin, and Aca: acacetin) inhibited cell proliferation in a variety of human cancer cell lines. These active flavonoids caused cell cycle arrest at G2/M phase and induced apoptosis and autophagy in human breast cancer cells. Molecular docking revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(163 citation statements)
references
References 39 publications
(33 reference statements)
7
142
1
3
Order By: Relevance
“…To further elucidate the mechanisms by which PLAC8 inhibits BC cell apoptosis, we examined the putative upstream regulators and downstream targets of PLAC8. The PI3K/AKT pathway not only plays a central role in cell cycle distribution, survival and drug sensitivity but also is associated with cell growth and apoptosis . Because these properties make the PI3K/AKT pathway a major candidate for investigating cell proliferation, we aimed to examine the potential relationship between PLAC8 and the PI3K/AKT pathway in BC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further elucidate the mechanisms by which PLAC8 inhibits BC cell apoptosis, we examined the putative upstream regulators and downstream targets of PLAC8. The PI3K/AKT pathway not only plays a central role in cell cycle distribution, survival and drug sensitivity but also is associated with cell growth and apoptosis . Because these properties make the PI3K/AKT pathway a major candidate for investigating cell proliferation, we aimed to examine the potential relationship between PLAC8 and the PI3K/AKT pathway in BC.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, PI3K/Akt pathway‐related transduction, including its mechanisms of activation, signal‐transducing molecules and effects on gene expression, contributes to tumorigenesis. Abnormal activation of the PI3k/AKT pathway is observed in numerous solid tumours, including BC, and this pathway controls a series of cellular processes, including cell proliferation, cell cycle, apoptosis, autophagy and cell migration. For example, miR‐613 acts as an upstream regulator that disturbs the interaction between YAP and WBP2, influencing the activity of the EGFR/PI3K pathway in triple‐negative BC cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids constituents are known for their antitumour activity such as inhibition of cell proliferation, adhesion and invasion, cell cycle arrest and apoptosis . A study analysing T kirilowii flavonoids (isorhamnetin, genkwanin and acacetin) effects on MCF‐7 human breast cancer cells showed that they induced cell cycle arrest at G2/M phase, apoptosis and autophagy through down‐regulation of PI3Kgamma‐mediated PI3K/AKT/mTOR/p70S6K/ULK signalling pathway …”
Section: Introductionmentioning
confidence: 99%
“…6 A study analysing T kirilowii flavonoids (isorhamnetin, genkwanin and acacetin) effects on MCF-7 human breast cancer cells showed that they induced cell cycle arrest at G2/M phase, apoptosis and autophagy through down-regulation of PI3Kgammamediated PI3K/AKT/mTOR/p70S6K/ULK signalling pathway. 7 Myricetin (3,5,7-trihydroxy-2-(3,4,5-trihydroxyphenyl)-4-chromenone) is a flavonoid widely found in vegetables, fruits and red wine. 8 This flavonoid presents several biological and therapeutic effects such as anti-inflammatory, antioxidant and antitumour.…”
Section: Introductionmentioning
confidence: 99%